2020
DOI: 10.1093/nop/npaa081
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sleep disturbance in the context of malignant brain tumors: a qualitative analysis

Abstract: Background Sleep is an important element in health-related quality of life of cancer patients and caregivers. This study aimed to explore the experience of sleep disturbance in people with malignant brain tumors (BT) and their family caregivers. Methods Participants were recruited from ambulatory neuro-oncology clinics. Semi-structured interviews were conducted with 24 patients (67% with high-grade gliomas) and 14 caregivers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Contributing to the care of a young cancer patient was not the sole cause of fatigue. Two studies cited difficulties associated with sleep [ 22 , 23 ]. The sleep of siblings was in some cases disturbed after the cancer diagnosis, given their concern about what the consequences of this disease might be on the patient [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributing to the care of a young cancer patient was not the sole cause of fatigue. Two studies cited difficulties associated with sleep [ 22 , 23 ]. The sleep of siblings was in some cases disturbed after the cancer diagnosis, given their concern about what the consequences of this disease might be on the patient [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…These difficulties primarily came from being busy with what had to be arranged for the patient (e.g., where the patient had to go or what medication had to be given). In addition, caregivers often had little time to rest between responsibilities, and therefore woke up earlier to complete all of their tasks [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, relatives’ involvement in a patient’s disease and treatment trajectory is associated with better patient health outcomes, including improved physical, cognitive, emotional, and psychological well-being; higher satisfaction with the quality of care and treatment; and greater patient safety, including feeling safer during hospitalization 23–26 . Involving patients and their relatives in treatment can substantially improve economic outcomes as well 19 . Different definitions and terminologies describe the concept of involvement , but in this review, we define involvement as relatives’ participation in making decisions about care and treatment, including sharing knowledge and information 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The burden on relatives is multifaceted, and research has shown that relatives often neglect their own physical, emotional, and social needs 14–17 . The most common symptoms reported by relatives are disturbed sleep, 18,19 stress, anxiety, 6,20 and social isolation 21 . Additionally, relatives of patients with an MBT experience a reduced quality of life compared with relatives of patients with other kinds of brain tumors 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, treatment developments have contributed to a markedly improved overall 5-year survival rate approaching 75% (Lannering et al, 2009 ; Gatta et al, 2014 ; Desandes et al, 2020 ). However, children now face significant long-term morbidity, including sleep disorders, with detrimental impact on everyday functioning and quality of life (Pickering et al, 2017 ; Jeon et al, 2021 ) that may be due to the tumor type, tumor location, or treatment (typically a combination of surgery, chemotherapy, and/or radiotherapy).…”
Section: Introductionmentioning
confidence: 99%